2016
DOI: 10.1002/ehf2.12109
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and hormonal markers under exercise training in patients with heart failure with preserved ejection fraction: results from the Ex‐DHF pilot study

Abstract: BackgroundOver 50% of patients with symptomatic heart failure (HF) experience HF with preserved ejection fraction (HFpEF). Exercise training (ET) is effective in improving cardiorespiratory fitness and dimensions of quality of life in patients with HFpEF. A systemic pro‐inflammatory state induced by comorbidities as the cause of myocardial structural and functional alterations has been proposed in HFpEF. ET modifies myocardial structure and has been related to inflammatory state. We investigated Ghrelin, relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Billebeau et al 22 observed a statistically significant (p<0.001) median decrease of 16% post-training (n=105), with no changes in control participants. In contrast, the post hoc analysis of the Ex-DHF pilot trial by Trippel et al 31 noted no significant treatment effect in patients with HFpEF.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Billebeau et al 22 observed a statistically significant (p<0.001) median decrease of 16% post-training (n=105), with no changes in control participants. In contrast, the post hoc analysis of the Ex-DHF pilot trial by Trippel et al 31 noted no significant treatment effect in patients with HFpEF.…”
Section: Resultsmentioning
confidence: 92%
“…One study by Trippel et al 31 reported on CT-proAVP levels and failed to find any statistically significant change post-training or compared with the control group in patients with HFpEF.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the definite impact of ET on diastolic function remains unclear and whether E/e′ is a key measure of diastolic function has to be discussed in the future. Substudies of the Ex‐DHF trial will therefore assess the effects of ET on inflammatory markers, metabolic parameters, collagen turnover, as well as on vascular function and ventriculo–arterial coupling, and novel non‐standard echocardiographic parameters of systolic and diastolic function.…”
Section: Discussionmentioning
confidence: 99%